Chronic alcohol intake increases the severity of pancreatitis induced by acute alcohol administration, hyperlipidemia and pancreatic duct obstruction in rats - Grauvogel, Jürgen; Grauvogel, Tanja Daniela; Ryschich, Eduard; Gebhard, Martha-Maria; Werner, Jens (Pancreatology, 2010)
Background: The mechanism of alcoholic pancreatitis is still unknown. It is of special interest why only about 5% of all alcoholics develop an episode of pancreatitis. We evaluated the role of long-term alcohol intake in the pathogenesis of alcoholic pancreatitis in rats. Methods:To evaluate the effect of long-term alcohol intake, rats were fed either a Lieber-DeCarli control diet (CD) or a Lieber-DeCarli alcohol diet (AD) for 6 weeks. Then, rats were infused over 2 h with either Ringer's solution (CO) or ethanol (E). In additional animals, alcoholic pancreatitis was induced by ethanol combined with hyperlipidemia and temporary pancreatic duct obstruction (EFO). Controls received Ringer's solution combined with hyperlipidemia and temporary pancreatic duct obstruction (RFO). Intravital microscopy (pancreatic perfusion and leukocyte adhesion), alcohol concentrations, amylase, lipase, cholesterine and triglyceride levels in plasma, myeloperoxidase activity and histology were evaluated at different time intervals. Results: In those animals which received the Lieber-DeCarli control diet, capillary perfusion was reduced in the E group and further reduced in the EFO group as compared to the controls (CO, RFO; p < 0.01). Leukocyte adhesion was significantly increased in rats receiving E (p < 0.01), and was further increased in the combination group EFO (p < 0.01). EFO induced histologically evident acute pancreatitis. The additional administration of a long-term alcohol diet further increased microcirculatory disturbances and pancreatic injury significantly (EFO-AD > EFO-CD). Conclusions: This study shows that alcoholic pancreatitis is induced by the combination of ethanol and individual cofactors. Chronic alcohol abuse intensifies these changes. Therefore, long-term alcohol intake seems to be a major factor in the pathogenesis of alcoholic pancreatitis.
Gesehen am 22.05.2023